Estética, cultura y política en la revista Criterio (Argentina, 1928-1936) - Miranda Lida (Centre de Recherches sur les Mondes Américains, 2015)
The magazine Criterio has been often studied as a clear manifestation of a catholic and anti-liberal publication, involved on the most important debates of its time. This article returns to this subject to illuminate new angles, as – for example – the refusal for the esthetic avant-gardes, as a clear reflex of its political alignments, as well as other cultural interventions. It can not be underestimated the fact that the review called herself a weekly of culture, according to the words of its director, Gustavo Franceschi. Magazine of rude debates, it was nevertheless recognized and read by prominent figures from the outside of the catholic field, as the socialist Alfredo Palacios, who has quotated articles by Gustavo Franceschi on his speeches in Congress. Those would allow us to explain why Criterio was an original expression of catholic press in the 1930´s.